Multi‐Band Tunable Chiral Metamaterial for Asymmetric Transmission and Absorption of Linearly Polarized Electromagnetic Waves. Issue 12 (11th October 2020) - Huang, Chen Xi; Zhang, Jing Jing; Wu, Lin; Zhang, Cheng; Yang, Jin; Yang, Liu Xi; Ke, Jun Chen; Bai, Lin; Cheng, Qiang; Cui, Tie Jun
Abstract: Due to the importance of chiral materials in realizing many exotic phenomena, a chiral metamaterial incorporated with active components of PIN diodes for the flexible control of asymmetric transmission (AT) of linearly polarized electromagnetic (EM) waves at microwave frequency is proposed. A transfer‐matrix approach and full‐wave simulations for cascading anisotropic impedance sheets is applied to analyse the physical mechanism of the structure, enabling the device with optimal multi‐band AT effect. The experimental results demonstrate that the robust real‐time controls of polarization conversion and AT effect for the linearly polarized waves can be achieved by altering the applied biasing voltage, giving rise to the tunability in three frequency bands of 9–10.5 GHz, 11–11.8 GHz, and 12.2–12.8 GHz. Furthermore, the tunable absorption can also be achieved, making it a good candidate in intelligent EM systems. Abstract : A chiral metamaterial incorporated with active components of PIN diodes is designed. A transfer‐matrix approach and full‐wave simulations for cascading anisotropic impedance sheets is applied to analyse the physical mechanism of the structure. The experimental results demonstrate the robust real‐time controls of polarization conversion and AT effect for the linearly polarized waves.